KEMAMPUAN BERBICARA SISWA SDN CIPAYUNG 02 PAGI DALAM PEMBELAJARAN BAHASA INDONESIA - Zahra Auliya; Fahrurrozi; Prayunigtyas Angger Wardhani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the level of speaking skills of fourth-grade students at SDN 02 Cipayung Pagi in Indonesian language learning under the Merdeka Curriculum. The importance of speaking skills as a foundation for literacy and active student participation is the main reason behind this problem. This is reinforced by initial findings that indicate that students' speaking skills are still lacking. Using a qualitative phenomenological method with 15 fourth-grade students as subjects, data collection was carried out through direct observation (presentation of story journals, questions and answers, discussions), interviews with teachers and students, as well as documentation and literature studies. Data analysis used the Miles, Huberman, and Saldana model. The results showed that all students (15 people) were in the "Fair" category with scores of 14-24, and none reached the "Good" category (score ≥ 25). The highest scores were achieved in the aspects of relevance, diction, mastery of material, and pronunciation. Suggested solutions are building self-confidence, practicing non-linguistic aspects, improving literacy, and involving the role of parents.